Physical Activity and Obesity Indicators: National Cross Sectional Study on Lebanese Adults - Soha Hourani; Nagham Hamadeh; Mohamad Al-Iskandarani; Sarine El Daouk; Maha Hoteit (International Journal of Public Health Science (IJPHS), 2017)
Association between higher levels of physical activity and lower rates of obesity has been shown. The aim is to assess the relation between the prevalence of physical activity and the Physical Activity Index (PAI) of 300 Lebanese healthy adults, with age, gender, occupation, body mass indices and waist circumferences (WC). The cutoff points of WC for both genders were determined using the values of Body Mass Index (BMI). A cross-sectional study using self-reported valid questionnaire was conducted randomly on 150 men and 150 women, between 18 and 74 years, from Beirut region. Association between variables was performed using chi2, T-Test and ANOVA. Linear regression determined the WC cutoffs based on BMI. 22% of the population was obese with WC mean level of 92.47±14.4cm (87.71±14.4 cm for women and 97.24±12.96 cm for men). The prevalence of physical activity was 34% in overall population (27% in women and 40% in men).There was no significant association between BMI values and PAI (p< 0.085 for men and p< 0.300 for women). However there was an inverse association between WC values and PAI in both genders (p<0.043 in men and p< 0.036 in women). Linear regression showed WC cut-off point in Lebanese women with BMI ≥25 kg/m2 and ≥30 kg/m2 of 86 cm and 100 cm respectively, whereas for men it was 92.12 cm and 105 cm respectively. The prevalence of physical activity in Beirut is low with differences among genders. The highest physical activity index is associated with the decreased values of waist circumference.